Co-operative aerial images: A geomedia history of the view from above. (November 2022) - Bender, Hendrik; Kanderske, Max
This article approaches aerial images from a media geographical perspective, tracing the development of three modes of seeing from above: historical aerial reconnaissance before and after the introduction of aerial photography; the advent of satellite-based remote sensing during the space age; and finally the development of drone-based imaging practices in the second half of the 20th century. Starting from the assumption that the aerial image is not a geomedium per se, but rather one that emerges as such through various co-operative processes of establishing geographical references with and within it, we draw on Goodwin's notions of "co-operative action" and Farocki's concept of "operative imagery" to theorize useful aerial images as co-operative images . Consequently, our historical analysis looks beyond the aerial image itself, taking into account the wider practices, infrastructures, and intended use cases involved in its operationalization.